2018
DOI: 10.1080/15548627.2018.1539590
|View full text |Cite|
|
Sign up to set email alerts
|

GRSF1-mediatedMIR-G-1promotes malignant behavior and nuclear autophagy by directly upregulatingTMED5andLMNB1in cervical cancer cells

Abstract: Emerging evidence has revealed that miRNAs could upregulate the expression levels of target genes. However, the molecular mechanism underlying upregulation of targets mediated by miRNAs remains unclear. In this study, we found a novel miRNA named MIR-G-1 by GRSF1-RNA immunoprecipitation (RIP)-deep sequencing, which could directly target and upregulate LMNB1 and TMED5 in a GRSF1dependent manner in cervical cancer cells. In addition, upregulated MIR-G-1 in cervical cancer promoted a malignant phenotype in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 67 publications
4
65
0
Order By: Relevance
“…However, research has con rmed that NST could not cure cancer. On the contrary, starvation makes cancer cells adapt to adverse conditions, and the surviving cells become more aggressive via EMT [5,26]. Our study con rmed that NST and silencing Akt1 promoted the EMT process of PCa cells.…”
Section: Discussionsupporting
confidence: 58%
“…However, research has con rmed that NST could not cure cancer. On the contrary, starvation makes cancer cells adapt to adverse conditions, and the surviving cells become more aggressive via EMT [5,26]. Our study con rmed that NST and silencing Akt1 promoted the EMT process of PCa cells.…”
Section: Discussionsupporting
confidence: 58%
“…5 Lamins, which are divided into A and B types, are located in the nuclear membrane and their main function is to stabilize the binding of protein and chromatin. 6 Recently, more and more studies have indicated that Lamin B1 are abnormally expressed in multiple types of tumors such as hepatocellular carcinoma, 7 colon cancer, 8 cervical cancer 9 and breast cancer. 10 These studies indicate that Lamin B1 can be used clinically as a novel tumor biomarker to guide physicians in developing treatment strategies and accurately predicting patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It indicated that overexpression of Lamin B1 might play an of vital role in malignant behavior of cervical cancer cells. 9 Except that, the AKT pathway plays a key role in the regulation of multiple cellular life activities such as proliferation survival, invasion and differentiation. 11 Many tumors including lung cancer promotes tumorigenesis and inhibits apoptotic signals by activating AKT pathway.…”
Section: Introductionmentioning
confidence: 99%
“…circRNA hsa_circ_0023404 was significantly upregulated in CC tissues compared to adjacent normal tissues. And, it enhances cervical cancer metastasis and chemoresistance through vascular endothelial growth factor A (VEGFA) and autophagy signaling by sponging miR‐5047 . GRSF1 (G‐rich RNA sequence binding factor 1) was originally identified as an RNA‐binding protein with high affinity for G‐rich sequences.…”
Section: Introductionmentioning
confidence: 99%
“…And, it enhances cervical cancer metastasis and chemoresistance through vascular endothelial growth factor A (VEGFA) and autophagy signaling by sponging miR-5047. 93 GRSF1 (G-rich RNA sequence binding factor 1) was originally identified as an RNA-binding protein with high affinity for Grich sequences. MIR-G-1 upregulates TMED5 and lamin B1 (LMNB1) in a GRSF1-dependent manner and promotes malignant behavior and nuclear autophagy in the cervical cancer cells.…”
mentioning
confidence: 99%